The influence of heavy metals to cytogenetic status of Plantago lanceolata L. - Atanasova, Marinela; Sekovski, Živko; Dimeska, Gordana; Mulev, Milto (Macedonian Journal of Ecology and Environment, 2003)
In purpose to investigate the influence of heavy metals (Cu, Cd, Pb and Zn) to mitotic index, mitosis, meiosis and fertility of pollen, seed material and flower buds has been collected from Plantago lanceolata, from the near area (100m) of melting factory MHK „Zletovo“ Veles R. Macedonia. Seed material and flower buds of the same plant from Gurište near the town Sveti Nikole has been considered as control material. Investigation of concentration of this heavy metals in the soil as well as in leaves of chosen plant showed 1.5 - 90 times larger amount in the area of melting factory „Zletovo“ Veles, compared to those in Gurište. That is why we expected and than confirmed the influence of those metals to cytogenetic status of investigated plant. Mitotic index of P. lanceolata has been significantly decresed, and the most frequently changes in mitotic cycle are: binuclear cells, micronuclei, cytomixis. The investigation of meiotic cycle shown high number of abnormal cells, which results in decrease of pollen fertility, and abnormal pollen.